Prerequisites for ethical leadership in health and social care: Integrative review - Seere, Anniina (Nursing ethics, 2026)
Health and social care organizations face structural reforms, workforce shortages, and increasing ethical demands. These pressures underscore the importance of ethical leadership, particularly from leaders managing complex services. While ethical leadership improves integrity, trust, and wellbeing, limited research has examined the prerequisites enabling its realization, especially from the perspectives of leaders in health and social care settings. Therefore, this integrative literature review aimed to identify and synthesize the prerequisites for ethical leadership in these contexts from a leadership perspective. The review was carried out following the PRISMA guidelines, with the protocol registered in PROSPERO and quality assessed using the Mixed Methods Appraisal Tool. A systematic search across six databases resulted in nine peer-reviewed studies (2010?2025). Inductive content analysis identified five categories of prerequisites for ethical leadership: (1) leader-centric prerequisites including ethical sensitivity and moral courage; (2) ethical organizational culture based on shared values; (3) leadership support such as mentoring and development; (4) ethical guidelines supporting consistent decision-making; and (5) resource sufficiency to enable ethical action. Ethical leadership emerged as both individual competencies and a dynamic process embedded in organizational structures. The ethical capacity of leaders was found to depend on personal capabilities and structural support. These findings inform leadership development and organizational strategies aimed at strengthening ethical practices in complex care environments.